Technologies Of Self-Diagnostication Of Future Teachers - Kholmatova Ziroat Anvarovna (Euro Asian Journal Publishing, 2024)
This article presents some thoughts on the technologies of selfdiagnosis of future teachers, their role in the educational process, methods of application, and positive impact on the educational process. The article also describes the conditions created for teachers in our country, as well as the issues of future teachers' work on themselves
Keywords: Diagnostics; self-assessment; development